Dicyano‐Substituted Diazaacenes. Issue 29 (2nd May 2017) - Müller, Matthias; Beglaryan, Stella S.; Koser, Silke; Hahn, Sebastian; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F.
Abstract: Herein, we report the synthesis, spectroscopic, and structural properties of novel 2, 3‐dicyano‐substituted azaacenes containing three to six annelated rings as a framework. The targets were prepared by Pd‐catalyzed coupling of diamino‐bis(tri‐isopropylsilylethynyl)benzene, ‐naphthalene, and ‐anthracene with either 4, 5‐dibromophthalonitrile or 6, 7‐dibromonaphthalene‐2, 3‐dicarbonitrile into the respective N, N ′‐dihydrodiazaacenes. Oxidation with MnO2 or PbO2 furnishes the dicyano‐substituted diazaacenes in reasonable to good yields. An exception is the diazahexacene, where the N, N ′‐dihydrodiazaacene is difficult to oxidize. Most of the targets could be crystallized and pack in isolated pairs, stacks, and brick‐wall motifs. The n‐type behavior of these molecules was illustrated in a proof‐of‐concept organic field‐effect transistor, showing mobilities up to 7×10 −3 cm 2 V −1 s −1 . Abstract : Control the flow : Different dicyano‐substituted diazaacenes were obtained by a Pd‐catalyzed coupling involving dibromophthalobenzene and dicyanodibromonaphthalene. The targets show attractive electrochemical and optical properties.